Rural Depopulation Pattern at Yogyakarta Special Province (DIY) - Baiquni, M; Muta’ali, Luthfi (Forum Geografi, 1998)
Rural population in Yogyakarta Special Province (DIY), in the last two decades, have shown dramatical changes in its quantity and quality. Depopulation is one of the interseting hanges which may considered as unique in term of its spatial distribution. Rural depopulation is a nebulous phenomenon which many factors, actors, and otherÂ phenomenon are involved in shoping depopulation. It is related to socio â economic hanges such as a) shifting economic structure and labour in rural areas from agricultural to non â agriculture sectors; b) growing urban economy leads by industry which may creates employment opportunities and adsorb labours or migrants; c) improving social development related to technological innovation, accessibility and resource availability. Besides the sicio â economic factors, physical geographycal factors may influence to depopulation pattern.This paper is based on a secondary data research i.e. statistical data at rural levels in Yogyakarta, thematics maps and other documents. Statistical methodes and map pattern analysis are employed to analysis data. The result of this research are as follows: a) the rural depopulation in DIY can be found in 189 rural areas of 393 rural areas (48.09%); b) the spatial distribution of the rural depopulation are in Gunung Kidul District (80 rural areas), Kulon Progo District (59 rural areas) Sleman District (33 rural areas), and Bantul District (17 rural areas); c) the rural depopulation in Yogyakarta at least related to six factors whih have been identified as out â migration, local resources, carrying capacity, geographycal location or accessibility, rural infrastructure, and service availability.